1976
DOI: 10.1002/jso.2930080502
|View full text |Cite
|
Sign up to set email alerts
|

Improved liquid cholesterol ester crystal thermography of the breast

Abstract: The infrated detection apparatus used in breast thermography is relatively costly and therefore is not widely available to less populated areas in the country. The use of liquid cholesterol crystals, applied to the breast (applied over a water-base black dye) has already been described in the literature as an effective substitute for infrared instrument thermography. This method, however, has been hampered by the time and troublesome effort necessary for removal of the substances upon completion of the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The technique has been used successfully to detect temperature elevations caused by malignant breast cancer (1,2,8,14), and temperature depressions caused by the entrapment of peripheral nerves and blood vessels (1 0, 13,15, 17, 19). Thetmography also has been used to detect deep vein thrombosis (6, 1 1, 18); vascular occlusion predictive of CVA (1 2,21,22); tissue death in instances of frostbite, diabetic ulcers, and bums (6,13,17,19,21); stress fractures (1,6); arthritis and bursitis (7,13); and tendinitis (3,5).…”
mentioning
confidence: 99%
“…The technique has been used successfully to detect temperature elevations caused by malignant breast cancer (1,2,8,14), and temperature depressions caused by the entrapment of peripheral nerves and blood vessels (1 0, 13,15, 17, 19). Thetmography also has been used to detect deep vein thrombosis (6, 1 1, 18); vascular occlusion predictive of CVA (1 2,21,22); tissue death in instances of frostbite, diabetic ulcers, and bums (6,13,17,19,21); stress fractures (1,6); arthritis and bursitis (7,13); and tendinitis (3,5).…”
mentioning
confidence: 99%
“…Liquid‐crystal thermography was first described by Fergason in 1964 1 . In the same year the procedure was also reported in the dermatologic literature by Crissey et al 2 Since then the method has found applicability in the detection of carcinoma of the breast, 3–6 in the study of abnormal venous patterns 7 including peripheral vascular disease and localization of incompetent perforator veins, 5 in placental localization, 5,8,9 in predicting the viability of pedicle flaps, 5,10 in measuring the therapeutic response to intra‐arterially injected reserpine, 11 in evaluating the effectiveness of sympathetic blockade, 12 in evaluating pulmonary disease, 5 in study of the pathophysiology of vitiligo, 5 and in detecting the presence of primary or metastatic carcinoma in the skin 4 …”
Section: Introductionmentioning
confidence: 99%